FEEL OF LOYALTY FOR OVO USERS IN KUPANG CITY - Maria Augustin Lopes Amaral; Engelbertus G. Ch. Watu; Simon Sia Niha (SEAN Institute, 2022)
Technology is a part of human life. Almost all mechanical work. The high use of smartphones makes the banking industry more competitive in marketing products using mobile phones, helping customers in the banking business everywhere and all the time. This research aims to analyze the impact of perceived service quality, perceived usefulness, perceived convenience, perceived security, and OVO users' satisfaction and trust. . This study classifies it as descriptive analysis with samples and questions as the main tools. The sample for this study is an e-cash user. Respondents were selected using non-probability and convenience sampling methods. The results of the analysis using the structural equation modeling (SEM) and the results will appear as follows: the results of agreement have a positive effect on satisfaction in use, perceived benefits in use have a significant effect on satisfaction in use. 4. The effect of perceived security has a positive effect on satisfaction in use, and the effect of satisfaction has a positive effect on justice in use